Analisis Pengaruh Kualitas Portal Akademik Universitas Malikussaleh terhadap Kepuasan Pengguna Menggunakan System Usability Scale (SUS) - Maksal Mina; Nurdin; Asrianda (Fakultas Teknik Universitas Hamzanwadi, 2026)
The Malikussaleh University Academic Portal is a web-based information system used to support various academic services, such as filling out the Study Plan Card (KRS), accessing the Study Result Card (KHS), class schedules, and other academic administrative information. However, several obstacles are still encountered in its use, such as less than optimal access speed, an interface that is not fully responsive, and navigation that is considered less intuitive by users. This study aims to evaluate the usability level of the Malikussaleh University Academic Portal using the System Usability Scale (SUS) method. The study used a quantitative approach with data collection techniques in the form of observation, interviews, literature studies, and distribution of SUS questionnaires to 50 active Malikussaleh University students selected using a purposive sampling technique. Data were analyzed based on the SUS calculation procedure which produces a usability score in the range of 0–100. The results showed that the Malikussaleh University Academic Portal obtained an average SUS score of 74.5. Based on the SUS interpretation, this value is included in the Good category, is on the Grade Scale B, and is included in the Acceptability Range Acceptable. These results indicate that the academic portal has a good level of usability and is acceptable to users. However, several aspects still need improvement, particularly system access speed, responsiveness on mobile devices, and simplified interface navigation. This research is expected to provide evaluation material for system administrators in improving the quality of digital-based academic services at Malikussaleh University.